Hypervalent iodine compounds for anti-Markovnikov-type iodo-oxyimidation of vinylarenes - Igor B. Krylov; Stanislav A. Paveliev; Mikhail A. Syroeshkin; Alexander A. Korlyukov; Pavel V. Dorovatovskii; Yan V. Zubavichus; Gennady I. Nikishin; Alexander O. Terent’ev (Beilstein Journal of Organic Chemistry, 2018)
The iodo-oxyimidation of styrenes with the N-hydroxyimide/I2/hypervalent iodine oxidant system was proposed. Among the examined hypervalent iodine oxidants (PIDA, PIFA, IBX, DMP) PhI(OAc)2 proved to be the most effective; yields of iodo-oxyimides are 34–91%. A plausible reaction pathway includes the addition of an imide-N-oxyl radical to the double C=C bond and trapping of the resultant benzylic radical by iodine. It was shown that the iodine atom in the prepared iodo-oxyimides can be substituted by various nucleophiles.